Industry perspectives on biomarker qualification - Lavezzari, G (Clin Pharmacol Ther, 2015)
Biomarkers have the potential to expedite drug development, increase patient safety, and optimize clinical response. Yet few have achieved regulatory qualification. A survey was conducted to clarify industry's perspective on biomarker qualification and identify the most promising biomarkers for drug development. The results across toxicities/clinical areas highlight challenges in regulatory qualification, although early prioritization and alignment on an evidentiary standard framework are key factors in facilitating biomarker development and qualification.